Gender-specific differences in associations of overweight and obesity with asthma and asthma-related symptoms in 30 056 children: result from 25 districts of Northeastern China. (June 2014) - Wang, Da; Qian, Zhengmin; Wang, Jing; Yang, Mingan; Lee, Yungling Leo; Liu, Fan; Liu, Miao-Miao; Zhao, Yang; Liu, Yu-Qin; Huang, Mei-Meng; Liu, Yang; Sun, Jing; et al.
Abstract Objective: The relationship between obesity and allergic respiratory diseases in childhood is still controversial. Furthermore, significant debate on the issue of whether or not gender modifies this association also exists due to inconsistent findings. The objective of this study is to evaluate the association between obesity and respiratory health in children, and to investigate the modifications of gender on this association. Methods: 30 056 children (aged 2–14 years) were randomly selected from 25 districts within 7 cities in Northeastern China in 2009. A standard questionnaire from the American Thoracic Society was used to characterize the childrens' histories of respiratory symptoms and illnesses. Child weight and height were measured, and obesity was calculated with an age and sex-specific body mass index. Results: The overall prevalence rates of obesity and overweightness were 14.08% and 12.32%, respectively. Compared to the children with normal body weights, asthma and asthma-related symptoms were more prevalent in overweight and obese children. Analysis stratified by gender showed that obesity was associated with more respiratory symptoms and diseases in females than in males. A significant association between obesity and diagnosed asthma [adjusted odds ratio (aOR) = 1.28; 95% confidence interval (CI): 1.02–1.60], as well as current wheezing (aOR = 1.46; 95%CI: 1.20–1.79) was found in females but not in males. Conclusions: There is an association between asthma symptoms and obesity in these Chinese children, and obesity had a significantly larger effect on females than males.